Women as Marginalized Beings: A Reflection on the Intersectionality of Marginalization within Indian Literary and Social Framework - Roy, Suparna; Mukherjee, Labanya Ray; Bhattacharjee, Prasenjit (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
As Elizabeth J. Meyer wrote in the book Queering Straight Teachers Discourse and Identity in Education is that, “Queer theory goes beyond exploring aspects of gay and lesbian identity and experience. It questions taken-for granted assumptions about relationships, identity, gender, and sexual orientation. It seeks to explode rigid normalizing categories into possibilities that exist beyond the binaries of man/woman, masculine/feminine, student/teacher, and gay/straight” (Meyer, 1). Among these series of complexly designed network of marginalization, which is a branched and towered regime of oppression in Indian framework, so, I select Gender and Caste as that lens to depict the narratives of marginalized identity- women. The concept of “women” as Judith Butler defines in her famous work Gender Trouble 1990- “Women are the sex which is not “one”. Within…a phallogocentric language, women constitute the unrepresentable…women represent the sex that cannot be thought, a linguistic absence and opacity” (Butler, 13). The identity of a woman gets trapped between some supposed and created links, which therefore my paper will try to discern, by the application of queer post-structuralist feminist theory, in both few selected literary texts- Mahasweta Devi’s Rudali and Breast Stories, Chitra Banerjee Devakaruni’s Mistress of Spices, Vine of Desire, and Sister of My Heart, and social context- women as subject of politics within the rape culture.